2021
DOI: 10.1166/jnn.2021.19013
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mesoporous Nano-Silica (SiO2) on Seed Germination and Seedling Growth of Wheat, Pea and Mustard Seed

Abstract: Wide range of nanomaterial applications is helpful to promote sustainable agriculture to the point of nanolevel. With regard to this, biocompatible silica nanoparticles have been used as a nanopriming agent for enhancing seed germination in rabi crops like wheat, pea and mustard. The current study was carried out in a completely randomized block design with four replications. One part of nanosilica (8 g/L) and three parts of Gibberellic acid (GA3) loaded nano-silica (100 ppm, 125 ppm and 150 ppm) were used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…As stated by [15], nanopriming has also been proven to have an effect on plant growth, stability, and physiology, in addition to modulating seed germination. Similarly, previous studies reported augmentation in plant growth of maize primed with TiO 2 NPs [44], rapeseed primed with ZnO NPs [41], fenugreek plants primed with Ag NPs [45], wheat, pea, and mustard primed with SiO 2 NPs [46], and chickpea primed with Fe 2 O 3 NPs [47]. Nanoparticles, as the main actors in plant morphology, growth, and physiology, affect physiological characteristics through changes in the formation of reactive oxygen species (ROS), peroxidase, superoxide dismutase (SOD), catalase (CAT), and enzymatic activities and modify leaf protein, chlorophyll, and total phenolic content (TPC) [48][49][50].…”
Section: Resultssupporting
confidence: 57%
“…As stated by [15], nanopriming has also been proven to have an effect on plant growth, stability, and physiology, in addition to modulating seed germination. Similarly, previous studies reported augmentation in plant growth of maize primed with TiO 2 NPs [44], rapeseed primed with ZnO NPs [41], fenugreek plants primed with Ag NPs [45], wheat, pea, and mustard primed with SiO 2 NPs [46], and chickpea primed with Fe 2 O 3 NPs [47]. Nanoparticles, as the main actors in plant morphology, growth, and physiology, affect physiological characteristics through changes in the formation of reactive oxygen species (ROS), peroxidase, superoxide dismutase (SOD), catalase (CAT), and enzymatic activities and modify leaf protein, chlorophyll, and total phenolic content (TPC) [48][49][50].…”
Section: Resultssupporting
confidence: 57%
“…It has been shown to boost seed germination, plant growth, and tolerance to biotic and abiotic stressors. For example, seed priming with silicic acid enhanced seedling development and germination rates in wheat plants exposed to salty environments [36]. Similarly, it was also reported that silicic acid priming enhanced early growth and salt stress resistance in pea, wheat, and rice seedlings [37].…”
Section: Discussionmentioning
confidence: 96%
“…Likewise, Alsaeedi et al 47 reported that all seedlings treated with SNPs had improved and higher germination characteristics and indices. Chourasiya et al 48 found that the percentage of seeds that germinated, the length of the shoots and roots, and the size of the seedlings were all significantly improved by nanopriming with nano-silica and nano-silica loaded with GA3. Recently, many studies supported applying nanosilica as fertilizer for crops where silica nanoparticles boosted the seed germination by their direct and indirect contribution in the growth of root and shoot 49 , 50 .…”
Section: Discussionmentioning
confidence: 99%